Genotype-Related Efficacy and Adverse Effects of Selective Serotonin Reuptake Inhibitors in Patients with Major Depressive Disorder (Precision Medicine Communications, 2022)
Major depressive disorder (MDD) is a major health condition that is amongst the foremost prevailing psychological state disorders worldwide and is extremely perennial and is the fourth foremost cause of disease burden. Despite the common mechanism of action, the drugs from within the same class exhibit variations, reportedly 60-70% of patients do not experience remission, and 30-40% of patients lack adequate response to drug therapy, resulting in non-adherence or discontinuation of therapy and prolongation of disease course. The variability of drug response is believed to be due to an individual’s variation in drug metabolism at the genetic level. This review accentuates the CYP450 enzymes (CYP2C19, CYP2B6, and CYP2D6), their single nucleotide polymorphism (SNPs), and their association with the antidepressants (selective serotonin reuptake inhibitors) efficacy or adverse effects.
Keywords: Major depressive disorder; selective serotonin reuptake inhibitors; single nucleotide polymorphisms; efficacy; adverse effects